The current state of the problem of in vitrogene pool preservation in poultry - Y. L. Silyukova; O. I. Stanishevskaya; N. V. Dementieva (Вавиловский журнал генетики и селекции)
This review presents the current progress in and approaches to in vitroconservation of reproductive cells of animals, including birds, such as cryopreservation and freeze-drying, as well as epigenetic conditions for re storing viable spermatozoa and female gametes after conservation. Cryopreservation is an effective way to preserve reproductive cells of various species of animals and birds. In vitrogene pool conservation is aimed primarily to the restoration of extinct breeds and populations and to the support of genetic diversity in populations prone to genetic drift. It is the combination of ex situ in vivoand ex situ in vitromethods that can form the basic principles of the strategy of animal genetic diversity preservation. Also, use of cryopreserved semen allows faster breeding in industrial poultry farming. Despite numerous advances in semen cryobiology, new methods that can more efficiently restore semen fertility after cryopreservation are being sought. The mechanisms underlying the effect of cryopreservation on the semen parameters of cocks are insufficiently understood. The review reflects the results of recent research in the field of cryopreservation of female and male germ cells, embryonic cells, the search for new ways in the field of genetic diversity in vitro (the development of new cryoprotective media and new conservation technologies: freeze-drying). Molecular aspects of cryopreservation and the mechanisms of cryopreservation influence on the epigenetic state of cells are highlighted. Data on the results of studies in the field of male reproductive cell lyophilization are presented. The freeze-drying of reproductive cells, as a technology for cheaper access to the genetic material of wild and domestic animals, compared to cryopreservation, attracts the attention of scientists in Japan, Israel, Egypt, Spain, and France. There is growing interest in the use of lyophilized semen in genetic engineering technologies. Methods of freeze-drying are developed taking into account the species of birds. Organizational and legal ways of solving the problems of in vitroconservation of genetic resources of farm animals, including birds, are proposed.